An Analysis of the Media Coverage of the Socio-Economic Impacts Generated by Online Tourist Rental Platforms - Martín Martín, José María; Prados-Castillo, Juan F; Jiménez Aguilera, Juan de Dios; Guaita Martínez, José Manuel (International Journal of Enterprise Information Systems, 2021)
This work aims to determine, by means of a press analysis, the positioning of the media on the problems generated by the growth of tourist pressure in city centers and by the expansion of tourist accommodation intermediated online. The main objective of this work is to analyze, classify, and group the main press media and agencies and their positioning with respect to their coverage of socioeconomic impacts linked to tourist accommodation platforms. Two different statistical techniques will be used, MultiDimensional Scaling and Hierarchical Ascending Classification (Clustering). Mainly, 24 impacts have been pinpointed, 12 positives and 12 negatives, which shows the great complexity of this phenomenon and the echo that the press makes of it. The impacts related to the ability to retain a dwelling in the tourist area are most frequently reported by the press, the increase in the price of rents/homes, the lack of regulation, the tourist pressure, or depopulation.
Keywords: impacts; media; rental platforms; Spain; Tourism; Emerging; Scopus